Respuesta :

Answer:

B

Step-by-step explanation:

Divide by pir^2 to get h all by itself and you'll have V/pir^2 = h

Edwena

[tex]\sf{\bold{\green{\underline{\underline{Given}}}}} [/tex]

⠀⠀⠀⠀

  • V = π r² h

______________________

[tex]\sf{\bold{\green{\underline{\underline{To\:Find}}}}} [/tex]

⠀⠀⠀⠀

  • Correct option = ??

______________________

[tex]\sf{\bold{\green{\underline{\underline{Solution}}}}} [/tex]

⠀⠀⠀⠀

V = π r² h

⠀⠀⠀⠀

  • Using equations formulae

⠀⠀⠀⠀

[tex]\sf \dfrac{V}{\pi} = r² h [/tex]

⠀⠀⠀⠀

[tex]\sf \dfrac{V}{\pi\times r^2} = h [/tex]

⠀⠀⠀⠀

  • checking correct option

⠀⠀⠀⠀

Option 1 :

⠀⠀⠀⠀

[tex]\sf \bigg( h = \dfrac{V}{\pi r^2} \bigg) \neq ( h = V - \pi r^2) [/tex]

⠀⠀⠀⠀

This option is not correct

⠀⠀⠀⠀

Option 2 :

⠀⠀⠀⠀

[tex]\sf \bigg( h = \dfrac{V}{\pi r^2} \bigg) [/tex] = [tex]\sf \bigg( h = \dfrac{V}{\pi \times r^2} \bigg) [/tex]

⠀⠀⠀⠀

This option is correct

⠀⠀⠀⠀

Option 3 :

⠀⠀⠀⠀

[tex]\sf \bigg( h = \dfrac{V}{\pi \times r^2} \bigg) \neq ( h = V\pi r² ) [/tex]

⠀⠀⠀⠀

This option is not correct

⠀⠀⠀⠀

Option 4 :

⠀⠀⠀⠀

[tex]\sf \bigg( h = \dfrac{V}{\pi \times r^2} \bigg) \neq ( h = V - \pi - r^2) [/tex]

⠀⠀⠀⠀

This option is not correct

______________________

[tex]\sf{\bold{\green{\underline{\underline{Answer}}}}} [/tex]

⠀⠀⠀⠀

  • Correct answer = option B
ACCESS MORE